Jurnal PKM Meningkatkan Pengetahuan Masyarakat Dalam Perbaikan Sanitasi Lingkungan - L.M. Azhar Sa'ban; Anwar Sadat; Asrul Nazar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service program is carried out in Mulyajaya Village, Lasalimu Selatan District, Buton Regency. Some of the main problems that become a problem in Mulyajaya Village, Lasalimu Selatan District, Buton Regency, are the not yet optimal knowledge of the community regarding Environmental Sanitation and the lack of optimal socialization to the public about how to create and improve a healthy environment. The results of this PKM activity can be described through the role of social capital as a form of local knowledge, it can be used as a means of socializing the importance of environmental awareness. The process of increasing community knowledge about environmental improvement is carried out through three discussions namely socialization, mentoring and planning for making garbage cans and making latrines.